Abdominal compartment syndrome as a complication of endoscopic carbon dioxide insufflation in a patient with malignant bowel obstruction: a case report - Taro Tanabe; Genki Tsukuda; Takahiro Hobo; Noboru Yokoyama; Haruhiro Inoue (Surgical Case Reports)
Abstract Background A self-expandable metal stent is often placed as a bridge to elective surgical treatment of left-sided malignant obstruction of the colon because it allows for primary anastomosis without the need for a temporary stoma, which has a positive impact on the patient’s quality of life. However, although a relatively safe procedure, colonic stenting can have complications that require emergency surgery. This case report describes a rare case of abdominal compartment syndrome that occurred as a complication of endoscopic insufflation during colonic stenting. Case presentation The patient was a 72-year-old woman who presented complaining of several days of constipation and loss of appetite. Computed tomography of the abdomen revealed obstruction of the sigmoid colon by a tumor. There were no symptoms or computed tomography findings to suggest perforation. Therefore, an attempt was made to insert a self-expandable metal stent. Acute respiratory disturbance and a change in consciousness occurred during the stenting procedure, with marked abdominal distention. Abdominal compartment syndrome was diagnosed and treated by decompressive laparotomy. Conclusions To the best of our knowledge, this is the first reported case of abdominal compartment syndrome as a complication of endoscopic insufflation during colonic stenting. The possibility of abdominal compartment syndrome should be considered if acute respiratory disturbance or altered consciousness occurs during endoscopic procedure in a patient with malignant bowel obstruction.